PENGARUH PARTISIPASI ANGGARAN DENGAN KOMITMEN, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA APARATUR PEMERINTAH KABUPATEN BONDOWOSO - Siwi, Ninit Dyah Pramarta; Kustono, Alwan Sri; Puspitasari, Novi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
Abstract: The objective of this research is to examine the influence of budget participation on performance, organizational commitment, organizational culture, and motivation; the influence of organizational commitment and organizational culture on performance; the influence of organizational culture on organizational commitment; and the influence of organizational culture on motivation of the government officers of Bondowoso Regency. The research sample consists of 180 government officers, including the structural officers and executive staff of the Local Government Work Unit of Bondowoso Regency. Data were analyzed using Structural Equation Modelling (SEM). Results show that budget participation has a positive and significant influence on performance, organizational commitment, organizational culture, and motivation; organizational commitment has a positive and significant influence on performance; organizational culture has a positive and significant influence on performance; motivation has a positive and significant influence on performance; and organizational culture has a positive and significant influence on organizational commitment. Keywords: Budget Participation, Performance, Organizational Commitment, Organizational Culture, Motivation.